INTERCULTURAL TRANSLATION: THE CASE OF TRANSLATING FIGURATIVE ASPECTS OF ENGLISH INTO INDONESIAN - Suhendra Yusuf (Universitas Galuh, 2020)
Figurative is used to enhance the effect of the statement or description (Kridalaksana, 1993). This figurative language is usually the style of language used by the author to express something unusual disclosure, that uses comparison, imagery, affirmation, sarcasm, contention, or something engagement with other things that attract the attention of readers. Figurative language used by the author with a view to turn the way of disclosure and the atmosphere so as to be meaningful discourse.